2020
DOI: 10.1038/s41598-019-56997-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of retinal blood vessels in patients with COPD during a pulmonary rehabilitation program

Abstract: cardiovascular diseases are frequently present in chronic obstructive pulmonary disease (copD). population-based studies found associations between retinal vessel diameters and cardiovascular health, but it is unknown whether this also applies to COPD patients. Therefore, we measured retinal vessel diameters in copD patients and aimed to determine the association with cardiovascular risk factors, lung function, and functional outcomes. In addition, we investigated whether an exercisebased pulmonary rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
(98 reference statements)
0
11
1
1
Order By: Relevance
“…COPD patients also had a larger FAZ diameter than healthy participants ( p = 0.002) ( 35 ), and there was a moderate correlation between partial pressure of oxygen (pO 2 ) and superficial/deep vascular density ( r = 0.559/0.800 respectively), and a highly negative correlation between pO 2 and FAZ size ( r = −0.876) ( 35 ), suggesting that retinal vascular density by OCTA may be useful to monitor disease progression in COPD patients ( 35 ). Retinal imaging in COPD has also shown that older age, higher systolic BP and lower levels of systemic inflammation are associated with narrower retinal venules ( p < 0.05) ( 36 ).…”
Section: Systemic Disturbances and Retinal Blood Flow In Non-septic S...mentioning
confidence: 99%
“…COPD patients also had a larger FAZ diameter than healthy participants ( p = 0.002) ( 35 ), and there was a moderate correlation between partial pressure of oxygen (pO 2 ) and superficial/deep vascular density ( r = 0.559/0.800 respectively), and a highly negative correlation between pO 2 and FAZ size ( r = −0.876) ( 35 ), suggesting that retinal vascular density by OCTA may be useful to monitor disease progression in COPD patients ( 35 ). Retinal imaging in COPD has also shown that older age, higher systolic BP and lower levels of systemic inflammation are associated with narrower retinal venules ( p < 0.05) ( 36 ).…”
Section: Systemic Disturbances and Retinal Blood Flow In Non-septic S...mentioning
confidence: 99%
“…COPD often occurs with some relevant cardiovascular comorbidities, such as arterial hypertension, heart failure, acute myocardial infarction, stroke, or peripheral arterial disease. These comorbidities largely contribute to Diagnostics 2024, 14, 950 2 of 13 increasing COPD's severity and accelerate the disease's progression, leading to progressive deterioration in quality of life, resulting in poorer clinical outcomes [3][4][5][6][7][8][9][10]. In-depth studies of this pathology and progress in our knowledge of the underlying pathogenetic mechanisms have led to evidence in the literature that support a strict correlation between chronic systemic inflammation, which characterizes COPD patients, and comorbidities that are commonly associated with COPD, especially cardiovascular comorbidities [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…COPD is a virtually untreatable disease; it is defined as chronic airflow obstruction, not fully manageable, and with an inevitable progression over time [5][6][7][8][9]. In this chronic lung disease, there is increased inflammation in the airways and pulmonary remodelling, often related to parenchymal destruction and primarily responsible for emphysema; in addition, mucous hyper-secretion and loss of elastic recoil are major events that are related to the development of airflow obstruction [6][7][8][9][10]. These mechanisms underlie the typical symptomatology of COPD, in particular dyspnoea, wheezing, fatigue, cough, and possibly sputum production [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По мнению ряда авторов, тяжелое клиническое состояние таких коморбидных пациентов и высокая смертность связаны с нарушениями функционирования сосудистого русла [3][4][5][6][7][8]. Как при ХСН, так и при ХОБЛ происходят изменения как в крупных сосудах, так и на уровне микроциркуляторного звена.…”
Section: Introductionunclassified